2020
DOI: 10.1016/j.isci.2020.101083
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Generation and Transcriptomic Profiling of Human iPSC-Derived Pulmonary Neuroendocrine Cells

Abstract: Expansion of pulmonary neuroendocrine cells (PNECs) is a pathological feature of many human lung diseases. Human PNECs are inherently difficult to study due to their rarity (<1% of total lung cells) and a lack of established protocols for their isolation. We used induced pluripotent stem cells (iPSCs) to generate induced PNECs (iPNECs), which express core PNEC markers, including ROBO receptors, and secrete major neuropeptides, recapitulating known functions of primary PNECs. Furthermore, we demonstrate that di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Tuft cells, originally described in the intestine as chemosensory cells that facilitate Th2 inflammation through their production of IL-25 and thymic stromal lymphopoietin (TSLP), have recently been identified as a rare airway EC type (identified by expression of POU2F3 ) ( 94 ). The role of pulmonary neuroendocrine cells (PNECs), present in bronchial airway epithelium (identified by expression of SYP , CHGA , PGP9.5 , ROBO2 , and ENO2 ), and their secretion of bioactive amines and peptides, remains poorly understood ( 95 ). The recently identified airway EC type ionocyte (co-expressing FOXI1 and CFTR ), although rare appears to be a major source of CFTR expression and function in the airway ( 86 , 88 ).…”
Section: Alveolar and Airway Ec Smentioning
confidence: 99%
“…Tuft cells, originally described in the intestine as chemosensory cells that facilitate Th2 inflammation through their production of IL-25 and thymic stromal lymphopoietin (TSLP), have recently been identified as a rare airway EC type (identified by expression of POU2F3 ) ( 94 ). The role of pulmonary neuroendocrine cells (PNECs), present in bronchial airway epithelium (identified by expression of SYP , CHGA , PGP9.5 , ROBO2 , and ENO2 ), and their secretion of bioactive amines and peptides, remains poorly understood ( 95 ). The recently identified airway EC type ionocyte (co-expressing FOXI1 and CFTR ), although rare appears to be a major source of CFTR expression and function in the airway ( 86 , 88 ).…”
Section: Alveolar and Airway Ec Smentioning
confidence: 99%
“…In adult mice, lineage tracing of basal cells using Krt5-creERT2, followed by single cell RNA-seq (scRNA-seq), revealed that new PNECs could originate from basal cells (Montoro et al, 2018). Consistent with this, culturing of human tracheal epithelial cells consisting almost exclusively of basal cells can give rise to PNECs (Hor et al, 2020). These findings suggest that tracheal PNECs can originate from basal cells.…”
Section: Pnec Lineage and Fate Specificationmentioning
confidence: 71%
“…Based on findings from PNEC development in mice, protocols have been developed to successfully generate PNECs from human embryonic stem cells (hESC) and induced pluripotent stem cells (iPSCs) (Chen et al, 2019;Hor et al, 2020). Notch signaling antagonists DAPT or DBZ were used in the last steps to derive PNECs from progenitors.…”
Section: Pnec Lineage and Fate Specificationmentioning
confidence: 99%
“…Lymphoblastoid cell line reprogrammed by Ichida Lab USC National Institute of Neurological Disorders and Stroke (NINDS) Biorepository, Coriell Institute ND00184 (original lymphoblastoid cell line) Healthy human lymphoblastoid cell-derived iPSCs (iPSC 2). Lymphoblastoid cell line reprogrammed by Ichida Lab USC National Institute of Neurological Disorders and Stroke (NINDS) Biorepository, Coriell Institute ND03719 (original lymphoblastoid cell line) Human foreskin fibroblast-derived iPSC line (FiPSC #3C15) Ryan Laboratory, USC Derived from BJ fibroblasts (ATCC, CRL-2522) Deposited Data Raw and analyzed iPNEC data Hor et al., 2020 GEO: GSE146990 Oligonucleotides (qPCR Primers) Gene Forward Primer Reverse Primer β-Actin 5′-CATGTACGTTGGTATCGAGGC-3′ 5′-CTCCTTAATGTCACGCACGAT-3′ HES1 5′-ACGTGCGAGGGCGTTAATAC-3′ 5′-GGGGTAGGTCATGGCATTGA-3′ HEY1 5′-AGAGTGCGGACGAGAATGGAAACT-3′ 5′-CGTCGGCGCTTCTCAATTATTCCT-3′ ASCL1 5′-CCCAAGCAAGTCAAGCGACA-3′ 5′-AAGCCGCTGAAGTTGAGCC-3′ GRP 5′-AAAGAGCACAGGGGAGTCTTC-3′ 5′-TCCTTTGCTTCTATGAGACCCA-3′ DLL3 5′-CGTCCGTAGATTGGAATCGCC-3′ 5′-TCCCGAGCGTAGATGGAAGG-3′ GAD67 5′-GCTTCCGGCTAAGAACGGT-3′ 5′-TTGCGGACATAGTTGAGGAGT-3′ ENO2 5′-CTGATGCTGGAGTTGGATGG-3′ 5′-CCATTGATCACGTTGAAGGC-3′ ROBO2 5′-GTTTGTGTTGCGAGGAACTATCT-3′ 5′-GTTTTGTCGGAAGTCATCTCGTA-3′ SYP 5′-CTCAGCATCGAGGTCGAGTTC-3′ 5′-GAGGAGTAGTCCCCAACTAAGAA-3′ SST 5′-CCCAGACTCCGTCAGTTTCT-3′ 5′-AAGTACTTGGCCAGTTCCTGC-3′ SV2 5′-TAGACCAGGCACTCATTGGC-3′ 5′-ACCCCTCCCCACAGTTACTT-3′ PENK 5′-TCTGAACCCGGCTTTTCCAA-3′ 5′-TACGCAAGCCAGGAAGTTGAT-3′ …”
Section: Key Resources Tablementioning
confidence: 99%
“…Therefore, a self-renewing source of patient-specific iPNECs facilitates the creation of reproducible human cellular models to study lung diseases characterized by PNEC dysfunction. For complete details on the use and execution of this protocol, please refer to Hor et al. (2020) .…”
mentioning
confidence: 99%